Creación y utilización de un archivo digital mediante el uso de la tecnología para la automatización de los documentos pedagógicos de los docentes de la unidad educativa “Sigchos” del cantón y parroquia Sigchos de la provincia de Cotopaxi - Jiménez Cárdenas, Marco Vinicio (2017)
This project consists on carrying out the digitization of some documents that teachers from Sigchos Educational Unit manage and it has for objective to allow the teacher’s work by using an application that contains templates of easy access and use which can give solution to many problems about managing a lot of information related to the students. There is an initiative to create one software that serves as tool to facilitate the teacher’s work, because a lot of them have many problems when they want to organize the information because they don’t have a reliable model when it is time to present the required information. After we obtained the results from the previous investigation, we can say that the institution doesn’t have a reliable digital file that allows to carry out the digitization of the information to facilitate the registration and handle the educational documents. For that reason, I developed an application that allows this task. For carrying out the project, I chose among several computer packages the program Microsoft office Excel because it is the most appropriate to manage. Also it allows to work in several pages related with the same file at the same time providing a great security in the appropriate using of the information. It is expected that the present project facilitates in a great form the files’ digitalization that are used in Ofimática applied to the educational purposes for being a great support for teachers. On the other hand, I hope that it provides valid data for the students, their parents and the authorities because it is an application that is easy to manage